Finding the pieces for the anaerobic methane oxidation jigsaw puzzle in mangrove wetlands. (March 2022) - Zhang, Manping; Dai, Yujie; Dai, Peiliang; Sun, Zekun; Lin, Xiaolan; He, Zhili; Tian, Yun
Abstract: Estuarine mangrove wetlands are generally considered a major source of methane (CH4 ) emissions. Anaerobic methane oxidation (AMO) is an important pathway for reducing CH4 emissions and is known to be tightly linked to carbon, nitrogen, sulfur and metal cycling processes largely driven by microorganisms. However, these coupled processes and their contributions to mitigating global warming remain unclear in mangrove wetlands. In this study, the depth-specific potential methane oxidation rates of nitrate-, nitrite- and nitrous oxide-dependent anaerobic methane oxidation (nitrate-, nitrite- and N2 O-AMO) and sulfate-dependent anaerobic methane oxidation (sulfate-AMO) processes were investigated using stable isotope tracing along with an assessment of the vertical nutrient and CH4 content profiles in mangrove sediments. The results indicated that nitrite-AMO, nitrate-AMO, N2 O-AMO and sulfate-AMO were active and exhibited methane oxidation rates varying from 24.1 to 1077.4, 14.1 to 66.1, 14.3 to 40.9 and 4.2–36.7 nmol CO2 g −1 dry soil d −1, respectively. Furthermore, nitrite-AMO and N2 O-AMO tended to be more active in the upper sediment layers, while nitrate-AMO and sulfate-AMO displayed higher rates in the deeper layers. The contribution rate of nitrite-AMO to the total of the 4 AMO processes examined in the mangrove sediments reached 28.90–95.80%, followed by nitrate-AMO (2.73–46.46%), sulfate-AMO (1.46–24.65%) and N2 O-AMO (1.70–4.47%), suggesting that the nitrite-AMO process is a significant methane sink in mangrove wetland ecosystems. The temporal and spatial variations in the nitrite-AMO bacterial depth and genus-specific distribution, abundance, activity and sensitivity to environmental factors were then investigated. The absolute abundances of the nitrite-AMO bacterial 16S rRNA and pmoA genes were 0.51–6.55 × 10 7 and 0.79–8.43 × 10 6 copies g −1 ds, respectively, and these values decreased with sediment depth; most of the samples were characterized as belonging to Group B of NC10. In addition, NO2 − is the limiting factor for nitrite-AMO bacteria in mangrove wetlands. Graphical abstract: Image 1 Highlights: DAMO and SAMO were widespread across sediment profiles in mangrove wetlands. NO2 − - and N2 O-AMO were more active in upper layers, contrary to NO3 − -AMO and SAMO. Nitrite-AMO contributes more to AMO than nitrate-, sulfate- or N2 O-AMO.